Los medios digitales como fuente de información de los jóvenes de Babahoyo en tiempos de pandemia - Alvarado Sánchez, Ronald Calixto (2020)
The final report's main objective is to analyze the use of digital media as a source of information for the youth of Babahoyo in times of pandemic, data that indicates the technological tools and digital media that young people use to access information. For the development of the project, various methods were used to complement the research, which, through surveys in a sample of 50 young people, proceeded to ask the respective questions, with the sole purpose of obtaining results and being able to add content in the conclusions and recommendations from the case analysis, in addition, the information obtained from the surveys was captured by means of the pie graph, to represent the results in the investigation. Through the documented research technique, it was possible to obtain information regarding digital media, with regard to its evolution, its importance, the types of digital media that exist, among others, content extracted from magazines and articles, based on its respective bibliographic source. Currently, digital media play a very important role in society, allowing many people to be informed and communicated from any device or technological tool, making the message emitted or received more effective and immediate, considering in this way, a communication factor used by young people from Babahoyo every Day.